Finite element analysis of tensile test for HDPE/EPR-MMT nanocomposite - Shaffiar, Norhashimah; Abdul Halim, Mohamad Khairi; Anuar, Hazleen; Majid, M. A. H. A. (Trans Tech Publications, Switzerland, 2015)
A small amount of nano dispersed filler leads to an improvement in material properties. Montmorillonite (MMT) is one type of filler commonly used in nanocomposite material. A high density polyethylene/ethylene propylene rubber - montmorillonite (HDPE/EPR-MMT) is one of the nanocomposite material that is new to the industry. This paper investigates the strength of HDPE/EPR-MMT nanocomposite under tensile loading. The experimental results of the tensile test on the nanocomposite will be compared with the tensile simulation in the Finite Element (FE) analysis for validation. The results showed that it is validated with relatively low percentage error of 0.01 % for the ultimate tensile strength and 0.18 % for the yield strength. The ultimate tensile strength of HDPE/EPR-MMT is 14.5 MPa and the yield strength is 13.2 MPa. By using MMT as a filler, the material strength is improved. The ultimate tensile strength of HDPE/EPR without filler is 11.45 MPa and the yield strength is 10.95 MPa.